Evaluation of the ethanolic extract of Mondai whitei (Hook.f.) Skeels for their antioxidant, anti-inflammatory and antidiabetic properties - Bayode, Mojisola Abosede; Ogunlakin, Akingbolabo D.; Gyebi, Gideon Ampompa; Ojo, Oluwafemi Adeleke (Edelweiss Applied Science and Technology, 2026)
This research evaluated the antidiabetic, antioxidant, and anti-inflammatory properties and phytochemical profile of the ethanolic extract from Mondai whitei roots via in silico, ex vivo, and in vitro approaches. The antioxidant activity (ferric-reducing power; DPPH radical scavenging, catalase, lipid peroxidation, and superoxide dismutase), antidiabetic activity (α-glucosidase and α-amylase inhibition), and anti-inflammatory effects (protein denaturation, proteinase inhibition, and membrane stabilization) were determined via in vitro tests. Ex vivo, liver homogenate was exposed to FeSO4-induced oxidative stress and treated with graded concentrations of the extract. The extract scavenged DPPH in a concentration-dependent manner and exhibited greater reducing power than ascorbic acid at 200 μg/mL. In FeSO4-treated tissue, the extract restored oxidative stress markers (malondialdehyde, SOD, and catalase) toward baseline, indicating protection against lipid peroxidation. The extract inhibited α-amylase (IC50 = 81.597 ± 0.776 mg/mL) and α-glucosidase, and demonstrated anti-inflammatory effects via the inhibition of protein denaturation, membrane stabilization, and proteinase inhibition (IC50 = 58.715 ± 1.996 μg/mL). HPLC identified seventeen compounds, with 2-chloro-4-methoxybenzaldehyde and vanillin being the most abundant. In silico docking of these constituents against α-glucosidase revealed that α-amylase, dipeptidyl peptidase IV strongly predicted the binding of chloropropacin, propacin, and yohimbine. Collectively, these findings suggest that the antidiabetic, antioxidant, and anti-inflammatory properties of M. whitei arise from its secondary metabolites, highlighting the role of the extract and its constituents as potential leads for managing diabetes and oxidative-stress–related inflammation.